Go Green - Rivers Nurture Us - Om Books International (Om Books International, 2020)
Why did ancient civilisations settle along the banks of Rivers? What makes the river Bank so lush Green and fertile? What is the riparian Zone? How do we get rain? How do rivers nurture life on Earth? Why did ancient civilisations settle along the banks of Rivers? What makes the river Bank so lush Green and fertile? What is the riparian Zone? How do we get rain? How do rivers nurture life on Earth? This vividly illustrated, delightful and informative book answers all your queries about rivers and makes you aware of their importance and the need to keep them free from pollution.
Keywords: How The World Works -- How The World Works; Sharing The Planet -- Sharing The Planet; Earth -- Earth; Natural Resources -- Natural Resources